2009
DOI: 10.1214/07-aos560
|View full text |Cite
|
Sign up to set email alerts
|

Support points of locally optimal designs for nonlinear models with two parameters

Abstract: We propose a new approach for identifying the support points of a locally optimal design when the model is a nonlinear model. In contrast to the commonly used geometric approach, we use an approach based on algebraic tools. Considerations are restricted to models with two parameters, and the general results are applied to often used special cases, including logistic, probit, double exponential and double reciprocal models for binary data, a loglinear Poisson regression model for count data, and the Michaelis-M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 32 publications
5
60
0
Order By: Relevance
“…Our assumptions are somewhat less restrictive and easier to check than those provided by Yang and Stufken (2009) for more general models. Our results were then applied to the proportional hazards parameterisation of the exponential regression model (1.1), for the cases of Type I and random censoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our assumptions are somewhat less restrictive and easier to check than those provided by Yang and Stufken (2009) for more general models. Our results were then applied to the proportional hazards parameterisation of the exponential regression model (1.1), for the cases of Type I and random censoring.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these results are not applicable to model (1.1). Yang and Stufken (2009) consider Loewner optimality and an even more general class of models. They obtain a series of excellent results, showing that under some conditions, for each given design there is always a design from a simple class which is better in the Statistica Sinica: Preprint doi: 10.5705/ss.2011.271 Loewner sense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yang and Stufken (2009), Yang (2010), and Dette and Melas (2011) convincingly demonstrated that unifying results for multiple models, multiple optimality criteria and multiple objectives can be obtained in the context of nonlinear models. They show that we can focus on a subclass of designs with a simple form, no matter what type of optimal designs we are looking for, including optimal multi-stage designs.…”
Section: Introductionmentioning
confidence: 97%
“…One may then restrict oneself to this subclass Ξ com . Along this line, a series of remarkable papers by Yang and Stufken (2009), Yang (2010), Dette and Melas (2011), Yang and Stufken (2012) and Dette and Schorning (2013) derived several complete classes of designs for single response models with respect to the Loewner ordering of the information matrices, based on considerations of admissibility and invariance.…”
Section: Introductionmentioning
confidence: 99%